The Impact of Noise Exposure on the Number of Primary Spermatocyte Cells in Mice (Mus musculus): An Experimental Study at UD Dua Saudara Demak - Purwito Soegeng Prasetijono; Dong-Ha Nam; Michael Adebayo (Frontier Advances in Applied Science and Engineering, 2024)
The utilization of machinery in the production process can increase output, but it also generates significant noise, potentially disrupting activities and causing noise stress. Noise stress can affect the spermatogenesis process. This study aims to investigate the effect of noise exposure on the number of primary spermatocyte cells in mice (Mus musculus) in the UD Dua Saudara Demak wood cutting environment. The study was conducted using mice as subjects, given the ethical and operative limitations on humans. Mice exposed to noise with an intensity of 90 dB for 35 days were divided into three groups: Treatment Group I (KP I) consisting of six mice using ear protective equipment (APT), Treatment Group II (KP II) without APT, and Control Group (KK) with 60 dB noise. Data were analyzed using One Way ANOVA and Bonferroni post hoc tests with a significance level of p<0.05. The results of the analysis showed the number of primary spermatocyte cells in the Control Group (KK) was 64.13 ± 1.99; KP I was 64.88 ± 1.45; and KP II was 51.88 ± 0.82. The One Way ANOVA test resulted in p=0.000, which indicates there is a significant difference between the two groups. Bonferroni post hoc test showed significant differences between KK and KP II, as well as between KP I and KP II, while there was no significant difference between KK and KP I (p=0.399). There is an effect of noise exposure on the number of primary spermatocyte cells in mice (Mus musculus) wood cutting.